Myofascial trigger points in subjects with non-specific neck pain (International Journal of Scientific Research and Management (IJSRM), 2021)
Background: In recent years, non-specific neck pain has become a frequent complaint due to poor head postures. It is characterized by Myofascial Trigger Points (MTrPs) in palpable taut bands of skeletal muscle that refer pain to a distance, and that can cause distant motor and autonomic effects. Objective. The aim of the study was to assess the prevalence of active and latent MTrPs in subjects suffering from non-specific neck pain in two hospitals, Sri Lanka. Method: This cross- sectional descriptive study was carried out among 31 patients with non-specific neck pain, presented to the department of physiotherapy, Teaching Hospital Peradeniya and National Hospital, Kandy, Sri Lanka. Participants were referred by a physician for non-specific neck pain and MTrPs were determined by a physiotherapist. MTrPs diagnosis criteria were the presence of a palpable taut band in a skeletal muscle; presence of a hyper-sensible tender spot in the taut band; local twitch response; reproduction of the referred pain pattern in response to compression; and spontaneous presence of the typical referred pain pattern and/or patient recognition. Results. The prevalence of MTrPs among patients with non-specific neck pain was 100%. Each of the 31 patients exhibited at least two MTrPs in the analyzed muscles. The mean number of MTrPs on each patient was 4.71± 2.036. MTrPs of the upper trapezius muscles were the most prevalent, in 96.8% of the participants. MTrPs in the suboccipital muscles, sternocleidomastoid, levator scapulae reached a prevalence of 58.1%, 45.2%, 35.5% respectively. 76.74% of total number of MTrPs in all analyzed muscles were active MTrPs. Conclusions. MTrP is a common source of pain in subjects presenting non-specific neck pain. Our study determined the presence of both active and latent MTrPs in this population with a higher prevalence of active MTrPs compared to latent MTrPs in all individual muscles.